EKSISTENSI PUTUSAN MAHKAMAH KONSTITUSI DALAM RANCANGAN UNDANG-UNDANG PEMILIHAN KEPALA DAERAH - Ainun Nisa, Miskha; Adhitya Widya Kartika (Jurnal Hukum Samudra Keadilan, 2025)
Indonesia will hold simultaneous regional elections on November 27, 2024. Before the Regional Elections were held, the Constitutional Court (MK) issued two rulings, namely No. 60/PUU-XXII/2024 and No. 70/PUU-XXII/2024 on August 20, 2024. This decision is related to the threshold for running for office and the minimum age requirement for candidate pairs in the Regional Elections. One day after the verdict was issued, the House of Representatives held a working meeting to revise the articles that had been decided by the Constitutional Court. This working meeting is considered an effort to annul the Constitutional Court's decision so that it becomes a polemic in the community. This research aims to find out the position and existence of the Constitutional Court's decision in the Election Bill. This study uses a normative juridical method with a literature study as a data collection method. The results obtained indicate that the cancellation of the revision of Law No. 10 of 2016 by the DPR shows that the decisions of the Constitutional Court (MK) are still being considered. The incorporation of the decisions of the Constitutional Court No. 60/PUU-XXII/2024 and No. 70/PUU-XXII/2024 into PKPU No. 10 of 2024 further clarifies the position and existence of the Constitutional Court's decisions within the Draft Regional Election Law.